Peningkatan Pengetahuan tentang Penyakit Jantung Koroner - Ambar Dwi Erawati (LPPM Akbid Harapan Ibu Pekalongan, 2021)
The disease that occurs in the elderly is hypertension. Meanwhile, hypertension has 81.3% risk factors for coronary heart disease. Coronary heart disease can be prevented with a healthy lifestyle, so it is necessary to increase knowledge about coronary heart disease in the elderly. Methods to increase knowledge about coronary heart disease through lectures which are a series of community service activities Assistance for elderly posyandu cadres in RW V, Bambankerep Village, Ngaliyan District, Semarang City. The results increased by 39.1% regarding definition, 21.73% regarding signs and symptoms, 28.3% regarding risk factors and 28.3% regarding the prevention of coronary heart disease.